2014
DOI: 10.1002/mrc.4080
|View full text |Cite
|
Sign up to set email alerts
|

Nonempirical calculations of the one‐bond 29Si–13C spin–spin coupling constants taking into account relativistic and solvent corrections

Abstract: The computational study of the one-bond (29)Si-(13)C spin-spin coupling constants has been performed at the second-order polarization propagator approximation (SOPPA) level in the series of 60 diverse silanes with a special focus on the main factors affecting the accuracy of the calculation including the level of theory, the quality of the basis set, and the contribution of solvent and relativistic effects. Among three SOPPA-based methods, SOPPA(MP2), SOPPA(CC2), and SOPPA(CCSD), the best result was achieved w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…A vast amount of structural studies of organosilicon compounds by means of 29 Si NMR is presented in the literature. , Nowadays, within the progress of theory of magnetic resonance parameters derived from a spin-Hamiltonian as the linear response functions, the question of the high-accuracy high-level computation of 29 Si NMR magnetic resonance parameters arises. In continuation of our previous results on the computation of 29 Si NMR chemical shifts, and 29 Si– 1 H and 29 Si– 13 C spin–spin coupling constants, in this paper we investigate the “environmental” relativistic effects of halogens in 29 Si NMR shielding constants of halosilanes.…”
Section: Introductionmentioning
confidence: 87%
“…A vast amount of structural studies of organosilicon compounds by means of 29 Si NMR is presented in the literature. , Nowadays, within the progress of theory of magnetic resonance parameters derived from a spin-Hamiltonian as the linear response functions, the question of the high-accuracy high-level computation of 29 Si NMR magnetic resonance parameters arises. In continuation of our previous results on the computation of 29 Si NMR chemical shifts, and 29 Si– 1 H and 29 Si– 13 C spin–spin coupling constants, in this paper we investigate the “environmental” relativistic effects of halogens in 29 Si NMR shielding constants of halosilanes.…”
Section: Introductionmentioning
confidence: 87%
“…Namely, these are the aug-cc-pVTZ-J basis sets of Provasi and Sauer [ 7 ] and the basis sets of Jensen’s series, (aug)pcJ- n ( n = 0–4) [ 8 , 25 ]. With these basis sets, the calculations of the silicon and phosphorus SSCCs of different types, in particular, J ( 29 Si, 1 H) [ 7 , 14 , 32 , 33 , 34 ], J ( 29 Si, 13 C) [ 35 ], J ( 29 Si, 19 F) [ 7 ], J ( 31 P, 1 H) [ 7 , 36 , 37 , 38 , 39 ], J ( 31 P, 13 C) [ 40 ], J ( 31 P, 17 O) [ 37 ], J ( 31 P, 15 N) [ 37 ], J ( 31 P, 19 F) [ 7 ], J ( 31 P, 33 S) [ 37 ], J ( 31 P, 77 Se) [ 37 , 41 ], and J ( 31 P, 125 Te) [ 41 ], were carried out mostly within the second-order polarization propagator approach (SOPPA) [ 9 ], including its coupled cluster-modified versions [ 9 , 42 ], and within the density functional theory (DFT) [ 43 ]. In a scant number of papers, it was shown that specialized J -oriented Jensen’s and Sauer’s basis sets for silicon and phosphorus do reproduce the results obtained using much larger basis sets with favorable accuracy [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%